Analyzing the Effect of Market Segmentation and Price on Purchase Interest of Batik Ciwaringin Products - Kadunci, Kadunci; Hartati, Tuti; Sudarno, Sudarno; Ginting, Riskon; Akbar, Djuni (International Journal Labs, 2023)
Background: Provide an adequate background covering the literature review and the gap of the research with other relevant former research works. Aim: This study aims to analyze the influence of market segmentation, price and interest in buying Batik Ciwaringin products, Cirebon Regency. Method: Data collection method using questionnaires to Ciwaringin batik buyers. The key informants in this study are consumers who buy Ciwaringin batik products. This research uses quantitative analysis techniques. Findings: The significance test t obtained market segmentation variable showed the t-count value = 3.772 > t-table = 1.996 with a significance value of 0.000<0.05. Thus, hypothesis 1 is accepted. The significance test t obtained the price variable showed the t-count value = 3.742 > t-table= 1.984 with a significance value of 0.000 < 0.05. Thus, hypothesis 2 is accepted. The result for free variables (market and price segmentation) was 92,203 with a significant rate of 0.000. While the Ftabel value at ? = 0.05 is 3.13, the variables of market and price segmentation simultaneously have a positive and significant effect on consumers' buying interest in Batik Ciwaringin. Thus, hypothesis 3 is accepted.